Skill-Mix Changes Targeting Health Promotion and Prevention Interventions and Effects on Outcomes in all Settings (Except Hospitals): Overview of Reviews - Claudia Bettina Maier; Juliane Winkelmann; Laura Pfirter; Gemma A. Williams (Frontiers Media S.A., 2023)
Objectives: Skill-mix changes to step up health promotion and prevention are increasing, but there is limited evidence on their effects.Methods: Overview of reviews, based on a protocol. The search was carried out in six databases, screening was performed ensuring high interrater reliability. All countries, health professions and lay workers in all settings (except hospitals) were included, quality appraisals performed.Results: A total of 31 systematic reviews were included. Expanded roles performing outreach (e.g., home visits) had mostly positive effects on access and health outcomes, primarily for hard-to-reach groups. Task-shifting in colorectal or skin cancer screenings (performed by advanced practice nurses) were suggested effective; supporting roles (by community health workers) increased uptake in screenings, but based on limited evidence. Expanded roles of various professions focusing on lifestyle modification showed promising effects in most reviews, including weight, diet, smoking cessation and physical activity. Reviews on cost-effectiveness were based on limited evidence.Conclusion: Promising skill-mix changes included expanded roles providing lifestyle modifying interventions, task-shifting, and outreach roles for hard-to-reach groups, whereas evidence on costs was limited.